Gaming the Past– Commercial Video Games with historical contexts: Evaluation of the Iranian Lotf Ali Khan Game - Mahdi Gheitasi; Joan Arnedo Moreno; Sorin Hermon; Marc Aurel Schnabel (Bina Nusantara University, 2023)
Virtual environments have numerous potentials for assisting the general public in experiencing cultural heritage, complementing current tools and practices centered on tangible goods such as museums, exhibitions, books, and visual content. Video games designed for educational purposes, which are becoming increasingly popular, have emerged as a new method of learning cultural content engagingly. The learning experience's specific goal distinguishes the educational use of video games. There is little doubt that we can learn from video games, but the more difficult questions about who, what, where, why, and how quickly we learn are not easily answered. This study examines the role of commercial video games in history learning and aims to enhance their effectiveness by analyzing their potential and limitations, using strategic planning and network analysis models. Through a case study on the Lotf Ali Khan game, it identifies strategies for improving history education through commercial video games. In this case study, it can be utilized to establish a conceptual framework for current trends in deployments of the past in historically focused video games, as well as a SWOT-ANP analysis to determine the major ways in which historical video games can aid in learning the subject matter under assessment. The data for this case study includes secondary sources and documents, fieldwork, observations, and semi-structured interviews with fifteen participants, as with other case studies (experts and children). Following the results, successful implementation occurs when a video game fully utilizes the following opportunities: antiquarian, monumental, and critical elements; wish story; composite imagination; borrowed authenticity; historical provenance; and legitimacy